DeMille and Danger: Seven Heuristic Taxonomic Categories of His Hollywood (Mis)Adventures - Anton Karl Kozlovic (European Journal of American Studies)
The legendary producer-director Cecil B. DeMille1 was an unsung auteur, a master of the American cinema, and a seminal cofounder of both Hollywood and Paramount Pictures who was professionally enamoured with the pursuit of sensationalism, authenticity and realism for his crowd-pleasing productions. Whilst pursuing this filmic quest, many of his crew were subjected to real danger, distress and injury, sometimes mortally. Utilising humanist film criticism as the guiding analytical lens, the critical DeMille, autobiographical and related anecdotal literature was selectively reviewed for illustrative instances of this infamous production penchant. Seven heuristic taxonomic categories were identified and explicated herein, namely: (1) Unexpected Working Accidents: From Annoying to Dangerous to Deadly, (2) Pain as a By-Product of Production: Expected and Unexpected, (3) Personal Discomfort as a Professional Norm: More Real Than Real?, (4) Professionalism as Expected Risk-Taking: Normalising Danger, (5) Miserliness and Rebellion: Managerial Risk-Taking, (6) The Engineering of “Accidents”: Applied Miserliness?, and (7) Bravely Leading from the Front: DeMille as Macho-Man. It was concluded from this montage of reported incidents that DeMille played a very colourful part in creating the factually-based legends of this never-to-be-repeated Golden Age of Hollywood. Further research into DeMille studies, the expansion of the above-constructed categories, and other autobiographical reminiscences about Tinsel Town is warmly recommended; whether as history, art or entertainment.